Melanotic Neuroectodermal Tumor of Infancy - Molla, Motiur Rahman; Ferdousi, Fahmida; Khaled, Ahmed (Pulse, 2014)
Two babys, one was 6 months old and another was 2 months old presented with a rapidly progressing melanotic neuroectodermal tumor of infancy (MNTI) in the maxilla. The tumor extended from the midline to the retromolar area of the left maxilla. It was confirmed as a melanotic neuroectodermal tumor through, radiology, cytology and histopathological examinations. The encapsulated tumor was excised .No recurrence was seen in the initial follow up nearly one year. DOI: http://dx.doi.org/10.3329/pulse.v5i1.20194 Pulse Vol.5 January 2011 p.61-65